Decline in tongue pressure during perioperative period in cancer patients without oral feeding. (February 2019) - Taniguchi, Hiroshige; Matsuo, Koichiro; Nakagawa, Kazuharu; Furuya, Junichi; Kanazawa, Manabu; Minakuchi, Shunsuke
Summary: Background and aims: Systemic muscle wasting during perioperative periods has a major impact on postoperative morbidity. However, data on oropharyngeal muscle weakness after surgery are scarce. We examined whether maximum tongue pressure (MTP) and hand grip strength (HGS) diminished during the perioperative period without and with oral feeding in patients receiving cancer surgery. Methods: A total of 258 patients undergoing cancer surgery who had visited a hospital dental clinic were prospectively recruited between October 2015 and February 2016. MTP and HGS were measured on the day before and 4 days after surgery. Data on age, sex, tumor location, surgical procedure, and oral feeding status were obtained from patient medical records. We analyzed for differences in the perioperative changes of MTP and HGS according to surgical procedure, oral feeding, and tumor location using ANOVA. Results: Neither MTP nor HGS differed significantly among tumor locations before surgery. The proportion of patients with an oral diet at 4 days after surgery was 36.7% and 34.5% for upper GI and colorectum groups versus 89.2% and 86.4% for genitourinary and lung groups, respectively. During the perioperative period, MTP decreased more significantly in patients without oral feeding than in those with oral feeding at 4 days after surgery (P < 0.01). HGS was not affected by postoperative oral feeding status. Both MTP and HGS decreased more significantly in the upper gastrointestinal group than in the genitourinary and lung groups (P < 0.05), except for MTP between upper GI and genitourinary groups (P = 0.10). Conclusions: MTP, but not HGS, diminishes significantly during the perioperative period without oral feeding. As tongue muscle disuse after surgery may adversely impact postoperative oropharyngeal muscle decline, perioperative tongue muscle strengthening exercises may assist in maintaining muscle strength and good oral feeding.